Rigid pavement design through structural dimensioning based in finite element method (Gaceta Técnica, 2016)
Mechanistic Methods are an excellent option when designing Structural Elements, due, among other things, to the precision simulating load conditions, the properties of the materials and support conditions. Depending on the nature of the situation to study, solving systems of equations generated from mathematical models of the phenomenon is often complex, these is why Numerical Methods are vital to get to these solutions. This research proposes the use of Finite Element Method to help in the structural dimensioning of rigid pavements, taking as example a stretch of the road network that is part of the Mass Transit System of Barquisimeto, Transbar, C.A (Transbarca). When getting the dimensioning of the pavement structure based on traffic information , conditions of foundation soil and the type of concrete used for the slab, according to the original project, the thickness of a rigid carpet was obtained similar to the one obtained when applying the AASHTO 86 Method. This Allows that the Method used in this research be validated when placed against the method most used in Venezuela for pavement design.
Keywords: mechanistic methods; finite element; AASHTO 86